Ownership networks and earnings inequality - Federico Huneeus; Borja Larrain; Mauricio Larraín; Mounu Prem (Inter-American Development Bank (IDB), 2022)
We use matched employer-employee data together with data on the ownership networks of Chilean firms to document a novel relationship between inequality in labor income and ownership structures. Exploiting transitions of firms in and out of networks, we show that network affiliation is associated with higher inequality along two dimensions. First, network firms pay higher average wages than standalone firms, increasing between-firm inequality. Second, the dispersion of wages within a network firm is higher than within a stand-alone firm, increasing withinfirm inequality. The effects are driven by increases in the wages of top workers, and by the entry of new top workers. Our findings shed light on the relationship between ownership structures and the distribution of labor income in the economy.
Keywords: G32; J31; 330; Earnings premium; Earnings inequality; Business groups; Ownership